Rayonnement solaire et environnement urbain : de l’héliotropisme au désenchantement, histoire et enjeux d’une relation complexe - Daniel Siret (Développement Durable et Territoires)
The connections between built environment and solar radiation vary throughout history. This paper proposes a historical overview of this evolution through architectural and urban theories, from the middle of the nineteenth century. The panorama thus displayed provides a basis for discussing the solar issue in sustainable city. This question is not only technical or economic, as it is most often discussed face to the energetic emergency, but it is also social and cultural. We develop the idea of a solar disenchantment, which is demonstrated by an increased technicisation, and privatization of our relationship to radiation.